Experience with clinical pathway for management of high grade blunt splenic injuries: a prospective study in adults at two tertiary trauma centers - Campbell, Don; Wake, Elizabeth; Grieve, John; Rashid, Muddassir; Wullschleger, Martin; Patel, Bhavik (International Surgery Journal, 2021)
Background: There is ambiguity regarding anatomical site of embolization, frequency of follow-up scans and splenic function following angioembolisation in the management of high grade blunt splenic injury. A splenic salvage pathway in patients who are hemodynamically stable or resuscitated to stability was introduced across two trauma centres. The aims of this project were: to develop a clinical pathway to manage hemodynamically stable blunt splenic injury patients and to determine rates of splenic salvage for patients with high grade splenic injury, assess complications and splenic function following completion of the pathway. Methods: Prospective study over a period of 24 months. Data was collected to evaluate rates of splenic salvage, complications and function of the spleen following angioembolisation. Results: Thirty-three patients, predominantly males (n=29) between the ages of 14-85 years, were included in the study. Three (9%) with grade V injury, underwent angioembolization on admission but required splenectomy as an inpatient. On day 14, all patients (n=30) with splenic salvage underwent blood tests, with 3 patients (9%) receiving vaccination for altered red cell morphology. The introduction of clinical pathway led to an increase in our splenic salvage rate to 91%. Conclusions: We believe that introduction of proposed clinical pathway may result in increased rates of splenic salvage with preservation of function following angioembolisation.